Cloning Full-Length, Cap-Trapper-Selected cDNAs by Using the Single-Strand Linker Ligation Method. (June 2001) - Shibata, Y.; Carninci, P.; Watahiki, A.; Shiraki, T.; Konno, H.; Muramatsu, M.; Hayashizaki, Y.
We have developed the single-strand linker ligation method (SSLLM), which uses DNA ligase to add a dsDNA linker to singlestranded (ss) full-length cDNA. The linkers have random 6-bp (dN6 or dGN5 ) 3′ overhangs that can ligate to any cDNA sequence, thereby facilitating the production of cDNA libraries with titers exceeding 1 × 10 6 independent clones. We confirmed that the 5′ ends of cDNA inserts cloned by using SSLLM are full-length and include the 5′ untranslated regions. The great advantage of our method is that the elimination of the GC tail simplifies the sequencing and protein translation of the full-length clones. Further, our method tags ss cDNAs more efficiently than does the traditional RNA ligase reaction.